Long-term follow-up of patients with cardiac syndrome X treated by spinal cord stimulation. Issue 5 (19th January 2007) - Angelo Sgueglia, Gregory; Sestito, Alfonso; Spinelli, Antonella; Cioni, Beatrice; Infusino, Fabio; Papacci, Fabio; Bellocci, Fulvio; Meglio, Mario; Crea, Filippo; Antonio Lanza, Gaetano
Abstract : Objective: To assess the long-term effect of spinal cord stimulation (SCS) in patients with refractory cardiac syndrome X (CSX). Methods: A prospective, controlled, long-term follow-up was performed of 19 patients with CSX with refractory angina who underwent SCS (SCS group, 5 men, mean (SD) age 60.9 (8.5) years); 9 comparable patients with CSX who refused SCS treatment (3 men, mean (SD) age 60.9 (8.8) years) constituted the control group. Clinical and functional status were assessed at the time of screening for SCS indication (basal evaluation) and at a median (range) follow-up of 36 (15–82) months. Results: The two groups at baseline did not show any difference in clinical characteristics and angina status. All indicators of angina status (angina episode frequency, duration and short-acting nitrate use) improved significantly at follow-up in the SCS group (p<0.001) but not in controls. Functional status, as assessed by the Seattle Angina Questionnaire and a visual analogue scale for quality of life, improved at follow-up in the SCS group (p<0.001 for all scales) but not in controls. Exercise tolerance, exercise-induced angina and ST segment changes also significantly improved in the SCS group but not in controls. Conclusions: Data show that SCS can be a valid form of treatment for long-term control of angina episodes in patients with refractory CSX.